The Role Of Law In Providing Decent Work For Citizens To Support The National Long-Term Development Plan 2025-2045 - Wijaya, Andri (DAS Institute, 2025)
This study discusses the role of law in fulfilling decent work for citizens to support the National Long-Term Development Plan (RPJPN) 2025-2045. The government always strives to provide and create decent jobs for its citizens, but unfortunately, the number of jobs is insufficient to meet the large number of prospective Indonesian workers. One reality on the ground is the widespread layoffs by companies for various reasons. As a developing country, layoffs have had various negative impacts on ongoing development. The high unemployment resulting from layoffs certainly has a systemic impact on the economy and development in Indonesia. The RPJPN 2025–2045 serves as the legal basis and primary guideline for all development actors—both government and non-government—in realizing Indonesia's grand vision by 2045, known as the